A randomised control trial comparing occupational therapy interventions that aim to improve developmental outcomes for HIV9positive children (aged 6 months - 5 years) on ART - Meissner, Robyn Jess (Division of Occupational Therapy, 2017)
Background: Antiretroviral treatment (ART) has reduced the mortality rate of HIV-positive children significantly, and is known to prevent the development and progression of HIV encephalopathy. However, even with ART, perinatal HIV infection places HIV-infected children at increased risk for encephalopathy and associated developmental delays. Research is lacking in the extent of developmental delay on children established on ART, along with evidence-based occupational therapy interventions to treat these developmental delays. A play-informed, caregiver-implemented, home-based group occupational therapy intervention (PICIHBI) presents one possible service delivery option to be explored. Aim: To determine whether children attending an experimental group (PICIHBI) versus children attending a control group (conventional, individual occupational therapy intervention) would present similar results in their total developmental quotient – on the Griffiths Mental Developmental Scales (GMDS) and Paediatric Functional Independence Measure (WeeFIM). Methods: A randomised control trial, which was pragmatic in nature and single-blinded, was used. The research population was all HIV-positive children, pre-formal school-going aged (6 months – 5 years), on ART attending the Groote Schuur Hospital paediatric HIV clinic at the time of the study. Caregiver and child dyads were randomly assigned to either the experimental or control group, and attended a monthly occupational therapy session. Differences in the GMDS and WeeFIM scores of each child after 5 and 10 months' intervention were compared. Results: Inter-rater reliability was established among the five researchers performing the GMDS before baseline assessments. Forty-two participants were recruited from a possible population of 72 participants and 39 participated in the baseline assessment. Twenty-eight participants completed mid and post assessments, 15 in the experimental PICIHBI group and 13 in the control group (90% power). Baseline averages on the GMDS showed the participants scoring at a borderline mental retardation level, with better performance in the locomotor and personal-social subscales, before interventions. Both groups had an average attendance of 5 sessions. Post-interventions, average total GMDS and WeeFIM scores between the two groups revealed similar scores within the predetermined non-inferiority margin and no significant differences at any time point. Conclusion: In conclusion, the low baseline scores confirm the need for occupational therapy intervention in pre-formal school-going HIV-positive children on ART. The PICIHBI intervention demonstrates a non-inferior impact in child development in this group compared to conventional, individual occupational therapy intervention. PICIHBI thus has potential for impacting occupational therapy practice in this field by providing an alternative equivalent treatment with increased reach.